The Expression Level of Inflammation-Related Genes in Patients With Bone Nonunion and the Effect of BMP-2 Infected Mesenchymal Stem Cells Combined With nHA/PA66 on the Inflammation Level of Femoral Bone Nonunion Rats - Huang, Y; Zhang, Q; Jing, Q; Li, X; Dong, F (Physiological research, 2024)
Bone nonunion delays fracture end repair and is associated with inflammation. Although bone nonunion can be effectively repaired in clinical practice, many cases of failure. Studies have confirmed that BMP-2 and nHA/PA66 repaired bone defects successfully. There are few studies on the effects of the combined application of BMP-2 and NHA/PA66 on bone nonunion osteogenesis and inflammation. We aimed to investigate the expression level of inflammation-related genes in patients with bone nonunion and the effect of BMP-2-infected mesenchymal stem cells combined with nHA/PA66 on the level of inflammation in femur nonunion rats. We searched for a gene expression profile related to bone nonunion inflammation (GSE93138) in the GEO public database. Bone marrow mesenchymal stem cells (MSCs) of SD rats were cultured and passed through. We infected the third generation of MSCs with lentivirus carrying BMP-2 and induced the infected MSCs to bone orientation. We detected the expression level of BMP-2 by RT-PCR and the cell viability and alkaline phosphatase (ALP) activity by CCK8 and then analyzed the cell adhesion ability. Finally, the levels of related inflammatory factors, including C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-alpha) and Erythrocyte Sedimentation Rate (ESR), were detected in nonunion rats. Our findings: The patients with nonunion had up-regulated expression of 26 differentially inflammatory genes. These genes are mainly enriched in innate immune response, extracellular region, calcium ion binding, Pantothenate and CoA biosynthesis pathways. The expression level of BMP-2 in the Lenti-BMP-2 group was higher (vs. empty lentivirus vector group: t=5.699; vs. uninfected group t=3.996). The cell activity of the MSCs + BMP-2 + nHA/PA66 group increased gradually. After being combined with nHA/PA66, MSCs transfected with BMP-2 spread all over the surface of nHA/PA66 and grew into the material pores. MSCs + BMP-2 + nHA/PA66 cells showed positive ALP staining, and the OD value of ALP was the highest. The levels of CRP, IL-6, TNF-alpha, and ESR in the MSCs + BMP-2 + nHA/PA66 group were lower than those in the MSCs and MSCs + nHA/PA66 group but higher than those in MSCs + BMP-2 group. The above comparisons were all P<0.05. The findings demonstrated that the expression level of inflammation-related genes increased in the patients with bone nonunion. The infection of MSCs by BMP-2 could promote the directed differentiation of MSCs into osteoblasts in the bone marrow of rats, enhance the cell adhesion ability and ALP activity, and reduce inflammation in rats with bone nonunion.
Keywords: Female; lidé středního věku; Animals; femur; Inflammation; kultivované buňky; Cells, Cultured; osteogeneze; Osteogenesis; mužské pohlaví; Rats; fraktury femuru; nezhojené fraktury; Rats, Sprague-Dawley; Fractures, Ununited; Humans; dospělí; mezenchymální kmenové buňky; kostní morfogenetický protein 2; zánět; Femoral Fractures; lidé; Middle Aged; Mesenchymal Stem Cells; zvířata; potkani Sprague-Dawley; Femur; ženské pohlaví; transplantace mezenchymálních kmenových buněk; krysa rodu Rattus; Mesenchymal Stem Cell Transplantation; Bone Morphogenetic Protein 2; Adult; Male